The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1107/s0907444904019109
|View full text |Cite
|
Sign up to set email alerts
|

A robotic system for crystallizing membrane and soluble proteins in lipidic mesophases

Abstract: A high-throughput robotic system has been developed for crystallizing membrane proteins using lipidic mesophases. It incorporates commercially available components and is relatively inexpensive. The crystallization robot uses standard automated liquid-handlers and a specially built device for accurately and reproducibly delivering nanolitre volumes of highly viscous protein/lipid mesophases. Under standard conditions, the robot uses just 20 nl protein solution, 30 nl lipid and 1 microl precipitant solution. 96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
150
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(154 citation statements)
references
References 7 publications
3
150
0
1
Order By: Relevance
“…Technologies for miniaturization of crystallization experiments are needed, but handling solutions of membrane proteins is complicated by their low surface tension and high viscosity. To address these challenges, both robotic (18,19) and microfluidic (20)(21)(22)(23) technologies have been developed to screen crystallization conditions on a submicroliter scale for both soluble and membrane proteins, but no universally applicable technology has yet emerged. Given the complexity of the problem of crystallization of membrane proteins, it is unlikely that a single technology would provide a universal solution, but there is a clear need for miniaturized technologies sufficiently robust, simple, and inexpensive to be accessible to individual laboratories.…”
mentioning
confidence: 99%
“…Technologies for miniaturization of crystallization experiments are needed, but handling solutions of membrane proteins is complicated by their low surface tension and high viscosity. To address these challenges, both robotic (18,19) and microfluidic (20)(21)(22)(23) technologies have been developed to screen crystallization conditions on a submicroliter scale for both soluble and membrane proteins, but no universally applicable technology has yet emerged. Given the complexity of the problem of crystallization of membrane proteins, it is unlikely that a single technology would provide a universal solution, but there is a clear need for miniaturized technologies sufficiently robust, simple, and inexpensive to be accessible to individual laboratories.…”
mentioning
confidence: 99%
“…With the assistance of A. Peddi and Y. Zheng, engineers at The Ohio State University where the original work was carried out, we were able to perform a proof-of-principle robotics exercise employing LabViewcontrolled motorized translation stages operating and supporting a microsyringe and a crystallization plate. With it, we demonstrated that the viscous mesophase could be dispensed automatically and wells were filled in such a way that eventually yielded crystals [19]. This was enough to secure funding for a robot which was custom-designed and built to our specifications.…”
Section: The In Meso Robotmentioning
confidence: 91%
“…Most of the above obstacles are diminished by the development of robotic systems and microfocus beams. Robotic crystallization technologies, which can dispense subnanoliter-scale drops in 96-well plates within minutes, have expended the use of the lipidic cubic phase by substantially increasing the number of crystallization conditions that can be explored with limited amounts of sample [72,85] . Another recent innovation is the microfocus beamline at synchrotrons [86] , which makes data collection from the undersized GPCR crystals possible.…”
Section: Bicelle Methodsmentioning
confidence: 99%